INTERFERON ALPHA (IFN-Α) AND LAMDA (IFN-Λ) ROLES ON HCV AND THE THERAPEUTICS OPTION - Ilham T Qattan (European Scientific Journal, ESJ, 2013)
Since the discovery of the hepatitis C virus, the goal of all treatment is to clear the virus and normalise the liver function, stopping the progression of the disease and thus reducing long-term complications of cirrhosis and hepatocellular carcinoma. The therapy for CHC used to consists of pegylated interferon alpha in combination with ribavirin and others new approved protease inhibitors, but still few of those treated can not achieved a compleat SVR. The reasons for failure are unknown, but may result from viral and host factors combined. The review here is to highlights and compare of what has been published previously.